The Effectiveness of Kahoot! in Enhancing Vocabulary Skills Among Sixth-Grade Students - Zuleha, Rahayu Nur; Hartono, Rudi; Rozi, Fahrur (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Vocabulary is a crucial aspect of language learning, impacting the four core skills: listening, speaking, reading, and writing. A strong vocabulary foundation enables students to understand spoken language, express their ideas effectively, comprehend texts, and produce well-structured written content. However, vocabulary acquisition remains a challenge for many students, particularly when conventional teaching methods fail to engage them, resulting in difficulties in memorization, lack of motivation, and monotonous learning experiences. To overcome these challenges, innovative strategies like gamification have been introduced to enhance engagement and learning outcomes. One effective approach is using Kahoot!, a game-based learning platform that integrates interactive quizzes and competition to make learning enjoyable. Research indicates that gamified learning environments boost motivation, participation, and vocabulary retention. This study explores the effectiveness of Kahoot! in improving vocabulary skills among sixth-grade students at SD Negeri Penggarutan 01 Brebes. A quantitative pre-experimental design was used, involving 18 students selected through purposive sampling. Vocabulary tests were conducted as both pre-test and post-test to measure the impact of Kahoot!, with data analysed using SPSS 22, including descriptive statistics and a paired sample t-test. Results showed a significant improvement in vocabulary scores, with the mean increasing from 72.50 in the pre-test to 79.17 in the post-test. The paired sample t-test yielded a significance value of 0.000 (p<0.05), confirming Kahoot!'s effectiveness. The study concludes that Kahoot! is a valuable tool for vocabulary learning, fostering motivation, participation, and retention.